Precalculus (6th Edition) Blitzer

Published by Pearson
ISBN 10: 0-13446-914-3
ISBN 13: 978-0-13446-914-0

Chapter 4 - Cumulative Review Exercises - Page 647: 1



Work Step by Step

Re-arrange as: $ x^2-3x-18=0$ $\implies x^2 +3x-6x-18=0$ $\implies x(x+3)-6(x+3)=0$ or, $(x-6)(x+3)=0$ So, $ x=-3,6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.